2013
DOI: 10.1001/jamasurg.2013.366
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Surgery

Abstract: Over the past decade, minimally invasive surgery has been introduced as a means to allow manipulation of delicate tissues with outstanding visualization of the surgical field. The purpose of this article is to review the available literature regarding early postoperative outcomes and the technical challenges of minimally invasive pancreaticoduodenectomy, including robotic techniques. Herein, we provide a retrospective review of all published studies in the English literature in which a minimally invasive pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…The robot offers advantages in terms of 3D vision, dexterity, and ergonomy [10]. Giulianotti and coworkers described the first robotic PD in 2003 [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The robot offers advantages in terms of 3D vision, dexterity, and ergonomy [10]. Giulianotti and coworkers described the first robotic PD in 2003 [11].…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of the robot increased the interest in many centers for minimally invasive pancreatic surgery, even in performing more complicated operations. The improved 3-dimensional imaging, the enhanced dexterity, the better visualization and increased magnification, and the improved ergonomics associated with robotic surgery [10] are some of the most important reasons for the development of robotic pancreatic surgery. The robot offers also the possibility of performing a minimally invasive operation in a way much more similar to traditional open surgery compared to the laparoscopic approach.…”
Section: Discussionmentioning
confidence: 99%
“…4-14 In fact, reduced blood loss, need for transfusion, and shorter hospital stays appear to be consistent advantages associated with laparoscopic PD (LPD). 15 Most recently, Kendrick et al reported that LPD performed for malignancy may be associated with improved long-term survival. 14 …”
Section: Introductionmentioning
confidence: 99%
“…The fact that the laparoscopic resection of the pancreatic head is performed exclusively in the highly specialized and high-frequency centers worldwide indicates the level of complexity and technical demands required for such procedures (9). The post-operative course was apparently different from the course of conventional open surgical procedures, namely, by the reduced time of patient's recovery due to minimal trauma, and the reduced time to getting the patient to a vertical position.…”
Section: Discussionmentioning
confidence: 99%
“…Operating time was slightly longer with laparoscopic procedures compared to the classical method and the number of post-operative days is lower in the laparoscopic compared to the conventional surgery (13). The percentage of post-operative complications is significantly reduced due to the non-existence of surgical wound infections (9). A minimally invasive approach is reserved for pathologically well-differentiated cases, with a clear picture of the surrounding infiltrations and anatomical variations.…”
Section: Discussionmentioning
confidence: 99%